Encore tricolore nouvelle 4 student book - Honnor, Sylvia; Mascie-Taylor, Heather ([S.l.] : Oxford University Press, 2014)
Encore Tricolore nouvelle edition builds on the success of Encore Tricolore and Tricolore. The new edition is exactly the right level for middle to high ability. The course now incorporates new features to bring it in line with the revised GCSE and Standard Grade specifications.